Exercise modulation of gut microbiota in Alzheimer’s disease: pathophysiological mechanisms and therapeutic perspectives - Leng, Si-yi; Yang, Qi-hang; Yuan, Yang; Chen, Bingao; Chen, Hongbao; Ban, Weikang; Zhang, Jiahao (Frontiers in Aging Neuroscience, 2025)
As global life expectancy increases, Alzheimer’s disease (AD) has become a major public health concern. The gut microbiota plays a pivotal role in regulating the central nervous system, influencing both behavior and cognitive functions in AD through direct and indirect mechanisms. Physical exercise has been shown to positively modulate the diversity and composition of the gut microbiota, emerging as a significant factor in slowing AD progression. A growing body of research highlights the dynamic interactions between exercise, gut microbiota, and AD, revealing that exercise can alter the synthesis and metabolism of key neuroactive substances, such as glutamate and aspartate, thereby enhancing cognitive function. Moreover, exercise influences peripheral and central immune responses via microbiota modulation, reducing neuroinflammation, amyloid-β (Aβ) deposition, and tau phosphorylation. Exercise also regulates gut microbiota-derived metabolites, including short-chain fatty acids (SCFAs), which are crucial for alleviating neuroinflammation and maintaining the integrity of the blood-brain barrier (BBB). This review synthesizes recent advances in the molecular mechanisms underpinning the exercise-microbiota-AD axis, offering new therapeutic perspectives for AD.